Critical perspectives on urban redevelopment - Gotham, Kevin Fox (JAI, 2001)
This is the fifth volume in a series which studies research in urban sociology, this work is an analysis of race and ethnicity in urban areas.
Keywords: Urban renewal.; Social research & statistics.; Urban communities.; Social Science -- Sociology -- Urban.; elektronické knihy; electronic books